Use of Covered Stents to Treat Coarctation of the Aorta - Qureshi, Shakeel Ahmed (The Korean Society of Cardiology, 2009)
Transcatheter treatments for coarctation of the aorta include balloon angioplasty and stent implantation. However, balloon angioplasty has its limitations and may be associated with complications, such as, recoarctation, dissection, and aneurysm formation, in adult patients. Bare metal stent implantation has offered an alternative during the last decade or so, but covered stents have been used with increasing frequency more recently, to the extent that covered stent implantation is the preferred treatment in correctly selected patients. Primary stent insertion, whether bare metal or covered, prevents elastic recoil of the aorta and may provide better and more predictable results than balloon angioplasty. Furthermore, stents are preferable for the treatment of complex aortic arch obstructions, but their usage is limited to older patients, because of limitations associated with growth.